2024
DOI: 10.1029/2023jf007389
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Bathymetry and Waves in Rip‐Channel Dynamics

D. F. Christensen,
B. Raubenheimer,
S. Elgar

Abstract: The behavior and predictability of rip currents (strong, wave‐driven offshore‐directed surfzone currents) have been studied for decades. However, few studies have examined the effects of rip channel morphology on the rip generation or have compared morphodynamic models with observations. Here, simulations conducted with the numerical morphodynamic model MIKE21 reproduce observed trends in flows and bathymetric evolution for two channels dredged across a nearshore sandbar and terrace on an ocean beach near Duck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The phase-resolving 3D numerical model Simulating WAves till SHore (SWASH) applies the nonlinear shallow water horizontal momentum equations and the nonhydrostatic vertical momentum equation using a finite difference scheme to simulate the water surface and velocity fluctuations (Zijlema, 2020;Zijlema et al, 2011). 3D models resolve the detailed physical processes required to best simulate wave transformations over complex bathymetry because depth-averaged (2D) models can underestimate nearshore flow velocities by neglecting nonlinear 3D dynamics (Christensen et al, 2024;Kumar et al, 2011;Marchesiello et al, 2015). Furthermore, a phase-resolving numerical model permits a direct comparison between XBR observations and modeling results (L. D. Szczyrba, Mulligan & Humberston et al, 2023).…”
Section: Numerical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase-resolving 3D numerical model Simulating WAves till SHore (SWASH) applies the nonlinear shallow water horizontal momentum equations and the nonhydrostatic vertical momentum equation using a finite difference scheme to simulate the water surface and velocity fluctuations (Zijlema, 2020;Zijlema et al, 2011). 3D models resolve the detailed physical processes required to best simulate wave transformations over complex bathymetry because depth-averaged (2D) models can underestimate nearshore flow velocities by neglecting nonlinear 3D dynamics (Christensen et al, 2024;Kumar et al, 2011;Marchesiello et al, 2015). Furthermore, a phase-resolving numerical model permits a direct comparison between XBR observations and modeling results (L. D. Szczyrba, Mulligan & Humberston et al, 2023).…”
Section: Numerical Modelmentioning
confidence: 99%
“…These strong offshore-directed rip currents can scour channels in nearshore sandbars and alter patterns in wave dissipation, causing the local mean water level to slope downwards toward the rip channel (Haller et al, 2002). In a study of the beach at Duck, North Carolina, Christensen et al (2024) found that the morphology of the ripchannel exerts a stronger control on flow dynamics than incident wave conditions. Feedback between the channel and the flow regime can further reinforce offshore currents and erode the beach profile (Komar & McDougal, 1988).…”
Section: Introductionmentioning
confidence: 99%